Estimation and distribution of exhaust ship emission from marine traffic in the Straits of Malacca and Singapore using Automatic Identification System (AIS) data - Saputra, Hendra (2013)
Global warming and air pollution have become one of the important issues to the entire world community. Exhaust emissions from ships has been contributing to the health problems and environmental damage. This study focuses on the Strait of Malacca area because it is one of the world’s most congested straits used for international shipping where located on the border among three countries of Indonesia, Malaysia and Singapore. The study seeks to estimate of the exhaust emission and to know the concentration of emission to several areas around. This is accomplished by evaluating the density of shipping lanes in the Straits of Malacca by using the data which obtained by Automatic Identification System (AIS). To show the movement patterns of ships, operational mode and influence of the ship movement to the distribution of emissions are integrating of AIS data and GIS software. MEET methodology is used to estimate emissions from ships and Gaussian Puff Model used to estimates the concentration in several areas around the Strait. The results show 813 total number of ships through the Strait of Malacca on 2 September 2011 at 07.00 am-08.00 am produces exhaust emission for NOx, CO, CO2, VOC, PM and SOx are about 13715.51 g/second, 25461.525 g/second, 11092.99 g/second, 5858.216 g/second, 415.304 g/second and 6921.746 g/second, respectively. The ships under the Singapore flag contribute approximately 22.72% of total emissions in the Strait of Malacca followed by Panama and Liberia flag approximately 21.32%, 12.89%, respectively. Ships under Malaysia and Indonesia rank of sixth and seventh respectively of the emission rates. The most high-risk areas which affected by the emissions are Sentosa Island (Singapore), Port of Pasir Gudang (Malaysia) and Jurong Island (Singapore) with approximately contaminated about 47.33%, 21.68% and 17.69%, respectively of total emission and other areas around the Strait represent below 1%.